2016
DOI: 10.4034/pboci.2016.161.34
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Glass Ionomer Cements (GIC) Restorations after Acidic Erosive Challenges:An invitroStudy

Abstract: Objective: To analyze the marginal adaptation of two different Glass Ionomer Cements (GIC) after erosive challenges. Material and Methods: Sixty sound extracted primary canines were selected and class V cavities were made. Teeth were allocated into 6 groups according to restorative material: 1) high-viscosity GIC (Ketac™Molar Easymix) and 2) resin-modified GIC with nanoparticles (Ketac™N100), low pH beverage erosive challenge (Orange juice and Coca-Cola) or distilled water as control. Thereafter the sample was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The behavior of materials in acid challenges depends on the chemical structure. Previous studies have also shown a tendency of surface degradation when these materials were exposed to acidic and alcoholic beverages action [ 38 , 39 , 40 ]. The consumption of soft drinks over a long period of time can induce erosive wear of restorative materials [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The behavior of materials in acid challenges depends on the chemical structure. Previous studies have also shown a tendency of surface degradation when these materials were exposed to acidic and alcoholic beverages action [ 38 , 39 , 40 ]. The consumption of soft drinks over a long period of time can induce erosive wear of restorative materials [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the included studies were in vitro studies published between 1993 and 2021. Of them, 1 study was conducted in Turkey [44], 1 in the USA [52], 1 in Egypt [27], 1 in Iraq [39], 1 in Indonesia [43], 2 in Belgium [48,49], 3 in Brazil [42,50,51] and 5 in India [40,41,[45][46][47]. The sample size varied from 15 to 200 teeth; a total of 1159 teeth were evaluated.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The prepared cavities were classified as Class V except in two studies, where Class I was also used [45,46], and in one study, where the authors performed restorations of bacterial artificial root caries [50]. The selected teeth varied, with 5 studies on extracted primary teeth [39][40][41][42][43] and 10 studies on extracted permanent teeth [27,[44][45][46][47][48][49][50][51][52]. Sound teeth were selected in most studies except one study on primary teeth [41] and one on permanent teeth [46], where caries teeth were selected.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations